Who writes a press release? Changing audience perceptions of journalists as marketers of news, not just reporters. (August 2021) - Fisher, Caroline; Park, Sora; Lee, Jee Young
The blurring of professional boundaries between journalism and other communications roles is a contested issue in journalism scholarship. To date, much of the work has examined this topic in relation to the impact of digitization on journalism practice, and the challenges this presents to traditional conceptions of journalistic professionalism. Less attention has been paid to audience perceptions of the shifting margins between traditional journalism and non-journalism roles. Data from the Reuters Institute Digital News Report 2018 found 26% of news consumers from 33 countries knew that the responsibility for writing a press release belonged to a spokesperson of an organization, rather than a lawyer (3%). However, 40% thought that it was the role of news reporters or producers and a further 34% said they did not know. Regression analyses reveal that news consumers in countries with higher online news consumption, use of news alerts, trust in news on social media and lower press freedom are less likely to answer correctly. Drawing on theory of advocacy in journalism this article argues these findings point to a possible perception on the part of the audience of journalists being both marketers and providers of news. We suggest this partly stems from journalists and news organizations increasingly assuming marketing functions to publicize themselves and their stories on social media and other digital platforms; and that this promotional activity helps blur the distinction between journalism as a news provider from public relations and other marketing roles in the eyes of the audience.